Forma de pago segura y aplicación del régimen para importar feldespato desde china por la empresa PAQUITO SA. - Mayon Medina, Manuel Mauricio (My University, 2019)
In the elaboration of this research work is detailed everything related to the process of negotiation between the parties involved in an international contract between which will proceed to make an exhaustive search on the import process and what is the customs regime that would suit you to the importing company as well as the safest and most adequate form of payment so that both parties are satisfied. As the main means to carry out the development of this research, the review and analysis of scientific articles, regulations and / or other legal documents that provide the necessary information to solve the problem raised in this investigation were resorted to; information was also collected from official sites such as the page of the National Customs Service of Ecuador (SENAE), Institute for the Promotion of Exports and Investments (PROECUADOR) and legal support of the Organic Code of Production, Trade and Investment (COPCI) ).
En la elaboración del presente trabajo de investigación se detalla todo lo relacionado al proceso de negociación entre las partes involucradas de un contrato internacional entre las cuales se procederá a realizar una búsqueda exhaustiva sobre el proceso de importación y cuál es el régimen aduanero que más le convendría a la empresa importadora como a su vez la forma de pago más segura y adecuada para que ambas partes queden satisfechas. Como principal medio para realizar el desarrollo de esta investigación se recurrió a la revisión y análisis de artículos científicos, reglamentos y/o demás documentos jurídicos que brinden la información necesaria para solucionar el problema planteado en esta investigación; también se recurrió a la recolección de información de sitios oficiales como la página del Servicio Nacional de Aduanas del Ecuador (SENAE), Instituto de Promoción de Exportaciones e Inversiones (PROECUADOR) y apoyo legal del Código Orgánico de la Producción, Comercio e Inversiones (COPCI).
Keywords: IMPORTACIÓN; RÉGIMEN ADUANERO; FORMA DE PAGO; NEGOCIACIÓN; CONTRATO INTERNACIONAL